2019
DOI: 10.1039/c8nr08724e
|View full text |Cite
|
Sign up to set email alerts
|

Pd–Co nanoalloys nested on CuO nanosheets for efficient electrocatalytic N2 reduction and room-temperature Suzuki–Miyaura coupling reaction

Abstract: The nanoalloy structure greatly improves the catalytic activity for electrocatalytic N2 reduction and Suzuki–Miyaura coupling reactions under ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In addition, some studies have shown that the catalyst activity can be further increased by using the synergistic effect of the two elements and loading the alloy on a support. Fu et al . successfully deposited bimetallic Pd–Co alloy nanoparticles on CuO nanosheets.…”
Section: Metal Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies have shown that the catalyst activity can be further increased by using the synergistic effect of the two elements and loading the alloy on a support. Fu et al . successfully deposited bimetallic Pd–Co alloy nanoparticles on CuO nanosheets.…”
Section: Metal Catalystsmentioning
confidence: 99%
“…In addition, some studies have shown that the cata-lyst activity can be further increased by using the synergistic effect of the two elements and loading the alloy on as upport. Fu et al [62] successfully deposited bimetallic Pd-Co alloy nanoparticleso nC uO nanosheets. Due to the synergistic effect, the bimetallic Pd-Co catalyst has higher catalytic activity than the single-metal (Pdo rC o) catalyst.…”
mentioning
confidence: 99%
“…The high-intensity deconvoluted peaks in the high-resolution spectrum of Pd 3d at binding energies of 335.8 and 341.1 eV correspond to the 3d 5/2 and 3d 3/2 electronic configurations of metallic Pd in Pd (1%)/CuFe 2 O 4 (Figure 4b). 54,55 The other two low-intensity peaks at binding energies of 336.8 and 342.3 eV are ascribed to the presence of Pd +2 , suggesting that very low concentration of Pd is present as PdO in the sample. 54,55 Similarly, the spectrum of Pd 3d present in Pd (5%)/NiFe 2 O 4 exhibits two sharp peaks associated with the 3d 5/2 and 3d 3/2 electronic configurations.…”
Section: Resultsmentioning
confidence: 99%
“…54,55 The other two low-intensity peaks at binding energies of 336.8 and 342.3 eV are ascribed to the presence of Pd +2 , suggesting that very low concentration of Pd is present as PdO in the sample. 54,55 Similarly, the spectrum of Pd 3d present in Pd (5%)/NiFe 2 O 4 exhibits two sharp peaks associated with the 3d 5/2 and 3d 3/2 electronic configurations. These peaks can be deconvoluted into four peaks associated with binding energies of 335.…”
Section: Resultsmentioning
confidence: 99%
“…Shen and co-worker developed Pd-Co nanoalloys nested on CuO nanosheets (Pd-Co/CuO) for efficient NRR. [214] At −0.2 V, it achieved 2.16% efficiency with 10.04 µg h −1 mg cat −1 NH 3 yield rate in 0.1 m KOH. The low results may be due to presence of Pd-Co over CuO reducing the active sites of CuO for N 2 selectivity.…”
Section: Cu Compoundsmentioning
confidence: 93%